Airway management of an unusual case of recurrent rhinoscleroma - Nita D'souza; Shilpa Kulkarni; Shama Bhagwat; Rusi Marolia (Wolters Kluwer Medknow Publications, 2011)
Rhinoscleroma is a rare entity encountered in anesthesia practice. We discuss the management of a patient after its recurrence, involving the upper respiratory tract i.e. nasopharynx and oropharynx, which compromised the airway. The pateint was referred for anesthesia on three different occasions with different presentations owing to the recurrence of symptoms.The presence of an oropharyngeal membrane with a small opening made airway management a challenge. The patient was successfully managed on all three occasions. Imaging facilitated assessment and subsequent airway management.